Short- and long-term responses to seasonal drought in ponderosa pines growing at different plantation densities in Patagonia, South America - Gyenge, Javier (2012)
Trees drought responses could be developed in the short- or in the long-term, aiming at sustaining carbon fixation and water use efficiency (WUE). The objective of this study was to examine short- and long-term adjustments occurring in different size Pinus ponderosa Dougl. ex P. & C. Laws trees in response to seasonal drought when they are growing under different competition level. The following variables were studied: branch and stem hydraulic conductivity, canopy and stomatal conductance (gc, gs), transpiration (E), photosynthesis (Amax), wood δ13C (as a proxy of intrinsic WUE), leaf to sapwood area ratio (AL:As) and growth in the biggest (B) and the smallest (S) trees of high (H) and low (L) density stands. AL:As was positively correlated with tree size and negatively correlated with competition level, increasing leaf hydraulic conductance in H trees. Accordingly, higher gc and E per unit AL were found in H than in L trees when soil water availability was high, but decreased abruptly during dry periods. BL trees maintained stable gc and E values even during the summer drought. The functional adjustments observed in H trees allow them to maintain their hydraulic integrity (no apparent ks losses), but their stem and leaf growth were severely affected by drought events. iWUE was similar between all tree groups in a wet season, whereas it significantly decreased in SH trees in a dry season suggesting that when radiation and water are co-limiting gas exchange, functional adjustments not only affect absolute growth, but also WUE.